On Approximately p-Wright Affine Functions in Ultrametric Spaces - Anna Bahyrycz; Janusz Brzdęk; Magdalena Piszczek (Journal of Function Spaces and Applications)
We prove some results for mappings taking values in ultrametric spaces and satisfying approximately a generalization of the equation of p-Wright affine functions. They are motivated by the notion of stability for functional equations.